Microwave Solid Phase Synthesis, Characterization and Antimicrobial Activities of Manganese(II) Complex with 2-((Furan-3-ylmethylimino)methyl)phenol - Xu, Suo-Ping; Cao, Ting-Ting; Wang, Si-Jia; Miao, Wei-Qing; Wu, Shu-Jie; Zhu, Ya-Nan (Asian Journal of Chemistry, 2015)
Mononuclear complex of manganese (1) has been designed and synthesized by 2-((furan-3-ylmethylimino)methyl)phenol (L) with MnCl2·4H2O in microwave radiation. The complex was characterized by X-ray crystallography, confirming that the central mangances(II) was coordinated by two oxygen atoms and two nitrogen atoms from two L. The complex was assayed for in vitro antibacterial (B. subtilis, S. aureus, S. faecalis, P. aeruginosa, E. coli and E. cloacae ) activities and showed better antimicrobial activity against Gram positive strains than Gram negative strains.